Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1103/physrevc.76.034601
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear reaction studies of unstable nuclei using relativistic mean field formalisms in conjunction with the Glauber model

Abstract: We study nuclear reaction cross-sections for stable and unstable projectiles and targets within Glauber model, using densities obtained from various relativistic mean field formalisms. The calculated cross-sections are compared with the experimental data in some specific cases. We also evaluate the differential scattering crosssections at several incident energies, and observe that the results found from various densities are similar at smaller scattering angles, whereas a systematic deviation is noticed at la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 34 publications
(67 reference statements)
2
41
0
Order By: Relevance
“…Hence, due to this simplification, we compromise a few MeV of binding energy in calculated values with experimental data, which does not affect the nuclear reaction cross sections, as reported in Ref. [26].…”
Section: Binding Energiesmentioning
confidence: 93%
See 3 more Smart Citations
“…Hence, due to this simplification, we compromise a few MeV of binding energy in calculated values with experimental data, which does not affect the nuclear reaction cross sections, as reported in Ref. [26].…”
Section: Binding Energiesmentioning
confidence: 93%
“…In some of our earlier work [26], it was shown that the Glauber model works remarkably well for RMF and E-RMF nuclear densities. The model reproduces experimental observables quite well for both the stable and unstable nuclei taken as targets and projectiles.…”
Section: Total Nuclear Reaction Cross Sections For Highly Neutron-ricmentioning
confidence: 96%
See 2 more Smart Citations
“…The density distribution of 30 Ne shows a small depression at the center indicating the structure of a bubble nucleus. Similar to our earlier calculations [15], the computer code can not use the density directly. So, we convert the densities into Gaussian form and calculate the Gaussian coef¿cients c i and a i using the relation:…”
Section: Resultsmentioning
confidence: 98%